Effectiveness of Single-Session Solution-Focused Therapy on Body Image Concern, Resilience, and Anxiety in Pre-Surgical Patients with Strabismus - Azemati, Mansoor; Ghamari, Mohammad; Gholami Toran Poshti, Marzieh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The aim of the present study was to examine the effectiveness of single-session solution-focused therapy on body image concern, resilience, and anxiety. Methods and Materials: The research method was quasi-experimental with a pre-test, post-test, and follow-up design with a control group. The statistical population included all patients with strabismus referred for pre-surgical consultation at Dr. Azemati’s clinic in Tehran in 2023. The sampling method was purposive, and the sample consisted of 45 participants who were randomly assigned to two experimental groups and one control group. The research instruments included the Littleton Body Image Concern Inventory (2005), the Beck Anxiety Inventory (1990), and the Connor-Davidson Resilience Scale (2003). Data were analyzed using mixed ANOVA. Findings: The results of the data analysis showed that single-session solution-focused therapy was effective in improving resilience and reducing anxiety among pre-surgical patients with strabismus, and this effect persisted during the follow-up phase (p < .05). This intervention may serve as an effective and rapid approach to managing negative emotions and enhancing psychological well-being in patients during the pre-surgical phase. Conclusion: Therefore, it is recommended that this type of therapy be systematically integrated into preoperative programs and considered as a complementary treatment option alongside other methods, to help patients face the surgical process with greater calm and achieve better outcomes.